2016
DOI: 10.1371/journal.pone.0168913
|View full text |Cite
|
Sign up to set email alerts
|

Conserved Lysine Acetylation within the Microtubule-Binding Domain Regulates MAP2/Tau Family Members

Abstract: Lysine acetylation has emerged as a dominant post-translational modification (PTM) regulating tau proteins in Alzheimer’s disease (AD) and related tauopathies. Mass spectrometry studies indicate that tau acetylation sites cluster within the microtubule-binding region (MTBR), a region that is highly conserved among tau, MAP2, and MAP4 family members, implying that acetylation could represent a conserved regulatory mechanism for MAPs beyond tau. Here, we combined mass spectrometry, biochemical assays, and cell-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 43 publications
(72 reference statements)
0
15
0
Order By: Relevance
“…We propose that tau aggregation may in turn promote HDAC6 coaggregation and inactivation of its catalytic activity, which would further amplify this cycle and lead to robust acetylated tau accumulation, as we and others commonly observe in AD brains. In addition to tau, HDAC6 reversibly regulates components of the actin remodeling machinery (e.g., actin and cortactin) 55 , a variety of MT-associated factors (e.g., tau, MAP2, and MAP4) 56 , heat shock signaling (e.g., Hsp70 and Hsp90) 36,57 , and more recently, stress granule (SG) formation by controlling liquid-liquid phase separation (LLPS) 58 . Therefore, HDAC6 inhibition could conceivably increase neuronal vulnerability by influencing tau processing as well as the stress response, mitophagy, autophagosome-lysosome fusion, and cytoskeletal remodeling.…”
Section: Discussionmentioning
confidence: 99%
“…We propose that tau aggregation may in turn promote HDAC6 coaggregation and inactivation of its catalytic activity, which would further amplify this cycle and lead to robust acetylated tau accumulation, as we and others commonly observe in AD brains. In addition to tau, HDAC6 reversibly regulates components of the actin remodeling machinery (e.g., actin and cortactin) 55 , a variety of MT-associated factors (e.g., tau, MAP2, and MAP4) 56 , heat shock signaling (e.g., Hsp70 and Hsp90) 36,57 , and more recently, stress granule (SG) formation by controlling liquid-liquid phase separation (LLPS) 58 . Therefore, HDAC6 inhibition could conceivably increase neuronal vulnerability by influencing tau processing as well as the stress response, mitophagy, autophagosome-lysosome fusion, and cytoskeletal remodeling.…”
Section: Discussionmentioning
confidence: 99%
“…In accordance with this observation, we found that hTau-4Q KI proteins bound to fly microtubules with a lower efficiency than both hTau-wt and hTau-4R isoforms in vivo . As mentioned above, it is likely that pseudo acetylation on multiple sites causes conformational changes, by possibly neutralising the positive charges of the lysines 27 , which are likely to induce modifications in hTau localisation, protein-protein interactions and phosphorylation in vivo , ultimately potentially regulating its bioavailability for microtubules. It is also possible that the specific increase in S262 phosphorylation, which adds a negative charge to hTau and is known to impair binding to microtubules 22 , accounts for the decreased affinity of hTau-4Q proteins for microtubules.…”
Section: Discussionmentioning
confidence: 99%
“…This discovery implies that acetylation of particularly KXGS motifs is an event possibly occurring merely in normal tau, but its role needs further investigation. In any case, the fact that other MAP proteins, such as MAP2, which share highly conserved repeats with tau, undergo lysine acetylation in the MBD and cysteine-dependent autoacetylation indicates that acetylation might be a conserved regulatory mechanism of MAP activity in governing cytoskeletal dynamics (Hwang et al, 2016 ).…”
Section: Tau Acetylationmentioning
confidence: 99%